Have All The Abangan Gone? Study The Existence of Muslim Abangan in Central Java - Nurul Ashfiya', Rofiqoh; Musonnif Alfi, Ahmad (Jurnal Studi Agama dan Masyarakat, 2025)
This study aims explore wether the Abangan Muslim community in Central Java, particularly in Blora, still exists and is growing or diseappered. Although previous studies have indicated the decline of Abangan religious practice, as Hefner puts it with his big question, “Where have all the Abangan gone?” field findings suggest otherwise. Using an ethnographic qualitative approach this article argues that several factors, including local government support, the role of community leaders, and the Samin community, influence the survival of the Abangan community in Blora. Further analysis shows these factors are interrelated and form a complex system in maintaining Abangan religious identity and practices amidst changing socio-cultural dynamics in the contemporary world.